(untitled) (Physical Education, Health and Social Sciences, 2025)
Blood collection and handling are foundational elements of clinical diagnostics, forming the basis for over 70% of medical decisions globally. Ensuring safety and following best practices during each phase, pre-collection, collection, and post-collection, are essential for reliable and accurate laboratory results. This review explores critical aspects of the blood collection process, focusing on minimizing errors, protecting both patients and healthcare workers, and maintaining specimen integrity. Pre-collection safety measures such as proper patient identification, equipment preparation, hygiene of the staff, and accurate site selection reduce the chances of contamination and ensure correct patient-sample matching. During collection, employing aseptic techniques, using the correct order of draw, selecting the appropriate blood tubes, and effective labeling are key to preserving sample quality and avoiding diagnostic delays. Patient comfort is also emphasized to improve compliance and reduce procedural complications. Post-collection handling addresses biohazard management, appropriate storage conditions, temperature control, and transport protocols that prevent hemolysis, clotting, or contamination. These practices reduce pre-analytical errors, which constitute a major proportion of total laboratory errors. The article further discusses challenges faced in clinical settings, including human error, insufficient training, needle-stick injuries, and improper transport procedures. Recent advancements such as the introduction of safety-engineered devices, barcode labeling, and digital tracking systems, have significantly improved process efficiency and safety. Guidelines from recognized bodies like the World Health Organization (WHO), Clinical and Laboratory Standards Institute (CLSI), and Centers for Disease Control and Prevention (CDC) are incorporated to support global standardization. By reviewing the latest literature and practice guidelines, this article provides a comprehensive resource for medical professionals. Adhering to these evidence-based protocols can substantially reduce diagnostic inaccuracies, safeguard healthcare providers from bloodborne pathogens, and ultimately enhance patient care and laboratory service quality.